The role of gene duplication and paralog specialisation in the evolution of the mammalian PRPS complex - Bibek R. Karki; Austin C. MacMillan; Sara Vicente-Muñoz; Kenneth D. Greis; Lindsey E. Romick; John T. Cunningham (Nature Communications)
Abstract The phosphoribosyl pyrophosphate synthetase (PRPS) enzyme catalyzes a chokepoint reaction in nucleotide production, making it essential for life. Here, we show that the presence of multiple PRPS-encoding genes is a hallmark trait of eukaryotes, and we find that gains or losses of paralogs are associated with major branching events in the eukaryotic tree. We pinpoint the evolutionary origins and define the individual roles for each of the mammalian PRPS paralogs, which we demonstrate work together as a heterogeneous multicomponent complex. Employing isogenic cells representing all viable individual or combinatorial assembly states, we dissect the basic organizational principles of the enzyme complex and characterize the emergent properties responsible for paralog specialization, including new modes of regulation that govern complex assembly and activity in vivo. Collectively, our study demonstrates how evolution has transformed a single PRPS enzyme into a biochemical complex endowed with novel functional and regulatory features that fine-tune mammalian metabolism.